KAJIAN OPTIMALISASI JARINGAN DISTRIBUSI AIR BERSIH (Studi kasus : PDAM Delta Tirta Sidoarjo Unit IPA Krian) - , Ratnanik ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Development of an area often gives either positive or negative effect. Creation of new district in some area requires the adequate infrastructure to support their activities, including infrastructure for water service. The needs for clean water can be done in several ways, such as using common piping system that is managed by the Regional Water Company (PDAM). The research was conducted on PDAM Delta Tirta Sidoarjo of IPA Units at Krian, by performing simulations with Waternet 2.2. Software. Network Billing data from PDAM Delta Tirta Sidoarjo of IPA unit at Krian is used to determine the existing data of amount of water consumption in 2012 (liters/person/sec), while the development is conducted by calculating the population projection and water demand projections based on Master Plan for Water Supply at Sidoarjo in 2011, then the results will be included in the node needs of customers. Simulation results from Waternet to existing network with fluctuated flow shows that the performance of the network system is not optimal yet. There is still laminar flow in 26 pipes and low pressure on the service node, that is 9.88 mH2O, such as at Sirapan, Kemangsen and Jagalan. Optimization of existing networks is conducted by enlarging the small diameter pipe from sub node of ôôôôôôôô ôôô ôôôôôôôôô¶ôô ôôôôôô ôôôôôôôôô ôô ôôôô ôôôôô ôôôô ôôôôôôôô ôôôô ôôôôôôôôôô ôôô ôôôô tank. Water discharge of pump no.2 must be set, also the head following the new tank. Optimization shows better result compared to the existing conditions due to efficient work of the pump for 14 hours in average, while the existing condition of the pump is working for 24 hours. Pressure left on the nodes after optimization is better because of an increase in pressure at all nodes, i.e. 11.53 mH2O.